REVIEW OF NON-HUMAN PRIMATES IN MALAYSIA: CONSERVATION STATUS AND THEIR DISTRIBUTION - Madinah, Adrus; Nur Aida, Md Tamrin (Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia, 2023)
The present report provides a summary and updates information on the non-human primates (NHP) species list, conservation status and their detailed distribution in Malaysia from a new multi-author published literature. There are five families of NHP in Malaysia, which includes nine genera and 24 species. For each species reported, their conservation status category based on IUCN and Malaysian laws were included. In order to make the data more informative, their distribution around Malaysia including Malaysian Borneo, their diet and habitats were also recorded and reported.